Supply Chain Optimization in Industry 5.0: An Experimental Investigation Using Al - Ivanovich Vatin, Nikolai; John, Vivek; Nangia, Richa; kumar, Manish; Prasanna, Y. Lakshmi (BIO web of conferences, 2024)
This experimental study examines the use of AI-driven supply chain management solutions in the framework of Industry 5.0. An analysis of fictitious data that represented product inventory, supplier details, customer orders, and transportation details showed significant cost savings in transportation logistics (10%), improvements in supplier cost efficiency (20%), and significant reductions in excess inventory (10%). In Industry 5.0, artificial intelligence (AI) emerges as a key technology that can promote effective, customer-focused, and sustainable supply chains.